2022
DOI: 10.1007/s00134-022-06833-8
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of pregnant women admitted to intensive care unit for severe pneumonia related to SARS-CoV-2 infection: the multicenter and international COVIDPREG study

Abstract: Purpose Management and outcomes of pregnant women with coronavirus disease 2019 (COVID-19) admitted to intensive care unit (ICU) remain to be investigated. Methods A retrospective multicenter study conducted in 32 ICUs in France, Belgium and Switzerland. Maternal management as well as maternal and neonatal outcomes were reported. Results Among the 187 pregnant women with COVID-19 (33 ± 6 years old and 28 ± 7 weeks’ gestation), 76 (41%) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 38 publications
9
58
2
2
Order By: Relevance
“…The search yielded thirteen relevant studies which fitted with our purpose ( Ehrmann et al, 2021 , Ferrando et al, 2020 , Ibarra-Estrada et al, 2022 , Jouffroy et al, 2021 , Kaur et al, 2021 , Kucukdemirci-Kaya et al, 2022 , COVIDPREG Study Group, 2022 , Vanderbilt Learning Healthcare System Platform Investigators, 2022 , PROFLO Study Group, 2021 , Tu et al, 2020 , Vianello et al, 2021 , Xu et al, 2020 , Yang et al, 2020 ). The search and selection strategies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded thirteen relevant studies which fitted with our purpose ( Ehrmann et al, 2021 , Ferrando et al, 2020 , Ibarra-Estrada et al, 2022 , Jouffroy et al, 2021 , Kaur et al, 2021 , Kucukdemirci-Kaya et al, 2022 , COVIDPREG Study Group, 2022 , Vanderbilt Learning Healthcare System Platform Investigators, 2022 , PROFLO Study Group, 2021 , Tu et al, 2020 , Vianello et al, 2021 , Xu et al, 2020 , Yang et al, 2020 ). The search and selection strategies are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… FiO2≤0.4 with flow ≤20 L/min to maintain SpO2≥90% for 2 h, need for non-invasive mechanical ventilation, death. HFNO/ APP group: lower intubation rate (30%) than HFNO (43%) RR=0.7, shorter length of stay (11% vs 13%) Peju et al ( Péju et al, 2022 ) France, Belgium, Switzerland 187 (8 HFNO/ APP) According to the severity of respiratory failure and local protocol. NA NA NA Pregnant patients.…”
Section: Resultsmentioning
confidence: 99%
“…In ähnlichen Fällen wäre für die meisten Schwangeren vermutlich zunächst die konventionelle Beatmungstherapie das geeignetere Vorgehen, um ein adäquates Sauerstoffangebot bereitzustellen. Allerdings zeigen Fallserien und Multizenterstudien, dass die Komplikationsrate für Mutter und Kind mit zunehmender Invasivität der Beatmung zunimmt [ 3 , 12 ].…”
Section: Diskussionunclassified
“…However, risk factors for ICU admission of pregnant patients diagnosed with COVID-19 are poorly explored. A retrospective multicenter study evaluated the management and outcomes of 187 pregnant women with COVID-19 admitted to several ICUs from Europe, and identified as risk factors for intubation obesity (cause-specific hazard ratio (CSH): 2.00, 95% CI: 1.05–3.80), p = 0.03), term of pregnancy (CSH: 1.07, 95% CI: 1.02–1.10), per + 1 week gestation, p = 0.01), extent of computed tomography (CT) scan abnormalities > 50% (CSH: 2.69, 95% CI: 1.30–5.60), p < 0.01) and non-invasive ventilation (NIV) use (CSH 2.06, 95% CI (1.09–3.90), p = 0.03) [ 15 ]. A recent case-control study showed that gestational diabetes also presented with a higher rate of ICU admission in SARS-CoV-2 pregnant patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%